Job satisfaction factors for housekeepers in the hotel industry: a global comparative analysis. Issue 1 (18th December 2020) - Andrade, Maureen Snow; Miller, Doug; Westover, Jonathan H.
Abstract : Purpose: This study offers a global comparative analysis of variables associated with job satisfaction, specifically work-life balance, intrinsic and extrinsic rewards, and work relations on job satisfaction for hotel housekeepers. Design/methodology/approach: The study analyzes these variants across 29 countries using International Social Survey Program data. Findings: Findings indicate significant differences in job satisfaction for hotel housekeepers across countries, lower job satisfaction for hospitality occupations compared to all other occupational categories, lower job satisfaction for hotel housekeepers than employees in other hospitality occupations, and a statistically significant positive impact of some elements of work-life balance, intrinsic and extrinsic rewards, and coworker relations on job satisfaction. Originality/value: The hospitality industry is characterized by poor work-life balance, high turnover rates and limited rewards. Hotel housekeepers report lower levels of satisfaction than other hospitality workers in terms of work-life balance, pay, relationships with managers, useful work and interesting work. Housekeepers play an important role in hotel quality and guest satisfaction. As such, understanding and addressing factors contributing to job satisfaction for hotel housekeepers is critical for managers